2015
DOI: 10.1016/j.tics.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Self: How Self-Reference Integrates Perception and Memory

Abstract: We propose a new account of how self-reference affects information processing. We report evidence that self-reference affects the binding of memory to source, the integration of parts into perceptual wholes, and the ability to switch from a prior association to new associations. Self-reference also influences the integration of different stages of processing, linking attention to decision making, and affects the coupling between brain regions mediating self-representation and attention to the environment. Take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
388
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 405 publications
(441 citation statements)
references
References 74 publications
41
388
5
7
Order By: Relevance
“…This runs counter to the view that exacerbated executive demands on older participants reduce matching performance on other-related stimuli, and thus increase the self-bias effect (cf. Sui & Humphreys, 2015a), but these findings in perceptual matching are consistent with prior studies of the self-referential effect on memory (Gutchess et al, 2010;Gutchess et al, 2007), suggesting maintained effects of self-reference at different stages of processing more generally.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This runs counter to the view that exacerbated executive demands on older participants reduce matching performance on other-related stimuli, and thus increase the self-bias effect (cf. Sui & Humphreys, 2015a), but these findings in perceptual matching are consistent with prior studies of the self-referential effect on memory (Gutchess et al, 2010;Gutchess et al, 2007), suggesting maintained effects of self-reference at different stages of processing more generally.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, activation of ventral brain regions is associated with self processing and attention (respectively in the ventro-medial prefrontal cortex [VMPFC] and the posterior superior temporal sulcus) when self-related stimuli are presented, whereas enhanced activation of a dorsal frontoparietal network is associated with attentional control when participants respond to stimuli related to a stranger. These data indicate that attentional-control processes are recruited more strongly in the latter condition (see Sui & Humphreys, 2015a, for a discussion). Additionally, neuropsychological studies have shown that brain lesion over the VMPFC abolishes self biases in memory, whereas brain damage in the dorsal attentional-control network that spares the VMPFC generates abnormally large biases toward self-related stimuli, due to an exaggerated effect of strong attentional signals (Sui, Enock, Ralph, & Humphreys, 2015).…”
mentioning
confidence: 81%
“…This research has established that simply training people to associate self-relevant words (i.e. their own name or the word ''You'') with particular shapes can lead to improved perceptual processing of those shapes (Sui, He, & Humphreys, 2012;Sui & Humphreys, 2015). Similar perceptual effects have also been found when the same items are associated with rewards, suggesting that the effect is due to the greater value people assign themselves compared to others (Sui et al, 2012).…”
Section: Associative Learningmentioning
confidence: 86%
“…The cognitive functions (working memory, attention, metacognition, and so forth) and neural circuits (especially prefrontal circuits) that underlie HORs are also required for conscious experiences involving the self, including emotional states involving the self (145,(156)(157)(158)(159)(160)(161)(162) Fig. 3 for HOT).…”
Section: A Modified Higher-order Theorymentioning
confidence: 99%